Chronic Stimulation of Leptin on Food Intake and Body Weight after Microinjection into the Ventromedial Hypothalamus of Conscious Rats (TAJ: Journal of Teachers Association, 2009)
A very low dose of leptin (50 ng) was microinjected into the ventro-medial hypothalamus (VMH) of each rat daily once for three days. Food intake and body weight were measured after leptin injections. Microinjection of leptin into the VMH reduced food intake by 33.3 % significantly (P